PENGARUH KUALITAS LAYANAN AKADEMIK DAN HARGA (BIAYA PENDIDIKAN) TERHADAP WORD OF MOUTH MELALUI KEPUASAN MAHASISWA SEBAGAI VARIABEL INTERVENING (STUDI PADA LPK SEKOLAH PERHOTELAN BALI) - Nyoman Surya Wijaya; Syahnur Said; Nengah Landra (Jurnal Ilmiah Hospitality Management, 2016)
In Indonesia, particularly in Bali, these are a lot of Training Centers (LPK) in tourism sectors which grow and evolve rapidly, by selling trend working on Cruise ship and over seas such as in hotels and restaurants, it is the main attraction for prospective students to continue their education after they have completed their educations in vocational or high school. The purposes of this study are to describe the effect of the quality of academic services to the student’s satisfaction, the effect of price (education expenses) to the student’s satisfaction, the influence of the quality of academic services to the word of mouth, the effect of price (education expenses) on word of mouth, the influence of the student’s satisfaction on word of mouth, the effect of the quality of academic services to the word of mouth through the students’ satisfaction, the effect of price (education expenses). The data analysis technique in this quantitative research using statistical analysis (descriptive statistics and inferential statistics es) to the word of mouth through the student’s satisfaction.). This research is analyzed by SEM with its analysis instrument the program Partial Least Square (PLS). In this research, it was found that: the quality of academic services and prices (education expenses) have positive and significant impact on the students’ satisfaction; quality of academic services have a positive and significance impact on word of mouth where students’ satisfaction have a role as full mediation, price (education expenses) have a positive and significance impact on word of mouth where students’ satisfaction have a role as partial mediation, price (education expenses) and the students’ satisfaction have positive and  significant effect on word of mouth, the quality of academic services have positive however there is non significance effect on word of mouth.